A Correlational Study Elevated Risk of Cardiometabolic Illness and the Prevalence of Obstructive Sleep Apnea Among the Population of Tebing Tinggi, North Sumatra, Indonesia - Raynaldo, Abdul Halim; Pase, Muhammad Aron; Ketaren, Andre Pasha (Journal of Endocrinology, Tropical Medicine, and Infectious Disease (JETROMI), 2023)
Background: Obstructive Sleep Apnea (OSA) is a prevalent sleep-related breathing issue, marked by repeated full or partial blockages of the upper airways. It's a primary respiratory condition that heightens the chances of cardiometabolic diseases. In our research, we explored the link between the increased risk of cardiometabolic ailments and the potential for OSA. Method: We studied 75 participants during community service activities and investigated the association between the high risk of cardiometabolic disease and the risk of OSA in the Society of Tebing Tinggi. We measured variables such as gender, age, weight, height, Body Mass Index (BMI), blood pressure, heart rate, random blood glucose, waist and neck circumference, and total cholesterol. Subsequently, we categorized the data and performed chi-square tests to analyze the associations between various factors and the risk of OSA. Variables with p<0.05 are considered eligible for multivariate analysis using binary logistic regression. Results: We identified 42 patients had a high risk of OSA (59.2%), while 33 patients had a low risk (40.8%). The study identified significant links between OSA risk and gender, age, blood pressure, and neck circumference (p-values <0.001, <0.001, and 0.01 respectively). In contrast, BMI, heart rate, glucose levels, waist size, and cholesterol did not show a significant connection to OSA risk. This indicates that while certain factors like gender, certain age groups, hypertension, and neck size are important in assessing OSA risk. However, BMI, heart rate, random blood glucose, waist circumference, and total cholesterol are not significant factors in determining the risk of OSA (p=0.2, p=0.4, p=0.2, p=0.1, p=0.9). Conclusions: Higher risk of cardiometabolic diseases (older age, gender, hypertension, neck size) was positively associated with the risk of OSA.